Self-formation of polymer nanostructures in plasma etching: mechanisms and applications. (15th December 2017) - Du, Ke; Jiang, Youhua; Huang, Po-Shun; Ding, Junjun; Gao, Tongchuan; Choi, Chang-Hwan
Abstract: In recent years, plasma-induced self-formation of polymer nanostructures has emerged as a simple, scalable and rapid nanomanufacturing technique to pattern sub-100 nm nanostructures. High-aspect-ratio nanostructures (>20:1) are fabricated on a variety of polymer surfaces such as poly(methylmethacrylate) (PMMA), polystyrene (PS), polydimethylsiloxane (PDMS), and fluorinated ethylene propylene (FEP). Sub-100 nm nanostructures (i.e. diameter  ⩽  50 nm) are fabricated in this one-step process without relying on slow and expensive nanolithography techniques. This review starts with discussion of the self-formation mechanisms including surface modulation, random masks, and materials impurities. Emphasis is put on the applications of polymer nanostructures in the fields of hierarchical nanostructures, liquid repellence, adhesion, lab-on-a-chip, surface enhanced Raman scattering (SERS), organic light emitting diode (OLED), and energy harvesting. The unique advantages of this nanomanufacturing technique are illustrated, followed by prospects.